2021
DOI: 10.1109/access.2021.3107479
|View full text |Cite
|
Sign up to set email alerts
|

Communication Among Heterogeneous Unmanned Aerial Vehicles (UAVs): Classification, Trends, and Analysis

Abstract: In the past decade, unmanned aerial vehicles (UAVs) have become a major research topic in robotics, despite their existence since 1915. UAVs can perform various activities efficiently and effectively; therefore, involving a group of UAVs in performing a certain task has become a growing research trend. Research involving multiple UAVs has been carried out in various areas such as force protection, warfare in the military, remote sensing, disaster response activities, and surveillance. While performing critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…In recent years, designing the collaborative systems of unmanned aerial vehicles (UAVs) commonly known as drones have become a major research topic in different areas, especially in robotics and artificial intelligence (AI) (C. Chen et al, 2018; Sultan et al, 2021). On the basis of available statistics, the worldwide commercial UAV market size is growing.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, designing the collaborative systems of unmanned aerial vehicles (UAVs) commonly known as drones have become a major research topic in different areas, especially in robotics and artificial intelligence (AI) (C. Chen et al, 2018; Sultan et al, 2021). On the basis of available statistics, the worldwide commercial UAV market size is growing.…”
Section: Introductionmentioning
confidence: 99%
“…An ad hoc network can be created with a group of flying UAVs; this is called a Flying Ad hoc Network (FANETs) of UAVs [3]. The different types of UAVs employed in various FANET scenarios can be classified based on such different factors as UAV size, weight, range, endurance, altitude, application, flying mechanism, ownership, airspace class, level of control (autonomy), and type of engine [4]. Recently, several studies have shown the importance of FANETs by investigating the integration of FANETs of UAVs with different technologies, including Virtual Reality (VR), [5][6][7][8][9], IoT [10][11][12], flying edge computing [13], flying fog computing [10,14,15], cellular networks [16][17][18][19], and flying cloud computing [20].…”
Section: Introductionmentioning
confidence: 99%
“…• UAVs: A multi-UAV system can be composed of homogenous vehicles, i.e., with identical features and capabilities, or heterogeneous vehicles, i.e., with different capabilities [38]. A key feature, especially for a multi-UAV system, is collision avoidance (CA).…”
mentioning
confidence: 99%